Monolithic Chip System with a Microfluidic Channel for In Situ Electron Microscopy of Liquids. (9th April 2014) - Jensen, Eric; Burrows, Andrew; Mølhave, Kristian
Abstract Electron microscopy of enclosed liquid samples requires the thinnest possible membranes as enclosing windows as well as nanoscale liquid sample thickness to achieve the best possible resolution. Today liquid sample systems for transmission electron microscopy (TEM) are typically made from two sandwiched microchips with thin membranes. We report on a new microfabricated chip system based on a monolithic design that enables membrane geometry on the scale of a few micrometers. The design is intended to reduce membrane deflection when the system is under pressure, a microfluidic channel for improved flow geometry, and a better space angle for auxiliary detectors such as energy-dispersive X-ray spectroscopy. We explain the system design and fabrication and show the first successful TEM images of liquid samples in the chips.